2020
DOI: 10.1038/s41598-020-68541-x
|View full text |Cite
|
Sign up to set email alerts
|

Species identification, phylogenetic analysis and detection of herbicide-resistant biotypes of Amaranthus based on ALS and ITS

Abstract: The taxonomically challenging genus Amaranthus (Family Amaranthaceae) includes important agricultural weed species that are being spread globally as grain contaminants. We hypothesized that the ALS gene will help resolve these taxonomic challenges and identify potentially harmful resistant biotypes. We obtained 153 samples representing 26 species from three Amaranthus subgenera and included in that incorporated ITS , ALS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The genus is the focus of weed scientific research 13 , because of these amaranth weeds posed a certain threat to agricultural ecology in the new habitat. A. palmeri and A. tuberculatus invade gradually into the new continents out of their origins, and were detected their resistant biotypes 14 . Accurate identification of these species is the basis of weed prevention and control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genus is the focus of weed scientific research 13 , because of these amaranth weeds posed a certain threat to agricultural ecology in the new habitat. A. palmeri and A. tuberculatus invade gradually into the new continents out of their origins, and were detected their resistant biotypes 14 . Accurate identification of these species is the basis of weed prevention and control.…”
Section: Introductionmentioning
confidence: 99%
“…1 ). Xu et al analyzed ITS, ALS (domain C, A and D) and ALS (domain B and E) and constructed topological trees 14 . In Waselkov et al studies, both nuclear and chloroplast sequences support the division of A. pumilus in subgen.…”
Section: Introductionmentioning
confidence: 99%
“…tuberculatus, the two species were almost indistinguishable [14][15] . In this study, it was found that there was only one SNP site difference in matK/trnK-UUU between A. arenicola and A. tuberculatus, while their ITS 14,20 and trnL-UAA sequences showed no difference 20 . In contrast, there are 46 SNPs and 144 InDels between A. arenicola and A. tuberculatus on chloroplast genomes.…”
Section: Discussionmentioning
confidence: 90%
“…The genus is the focus of weed scienti c research 13 , because of these amaranth weeds posed a certain threat to agricultural ecology in the new habitat. A. palmeri and A. tuberculatus invade gradually into the new continents out of their origins, and were detected their resistant biotypes 14 . Accurate identi cation of these species is the basis of weed prevention and control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation